2002
DOI: 10.1046/j.1523-536x.2002.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth Position, Accoucheur, and Perineal Outcomes: Informing Women About Choices for Vaginal Birth

Abstract: Findings contribute to growing evidence that birth position may affect perineal outcome. Women's childbirth experiences should reflect decisions made in partnership with midwives and obstetricians who are equipped with knowledge of risks and benefits of birthing options and skills to implement women's choices for birth. Further identification and recognition of the strategies used by midwives to achieve favorable perineal outcomes is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 15 publications
8
58
1
11
Order By: Relevance
“…Some other benefits include better perineal muscle relaxation, greater feeling of control and safety over the situation, less abrupt and better transition from the uterus to the environment and a significant risk reduction of vaginal tearing (Dahlen et al, 2013;Shorten, Donsante, & Shorten, 2002;Edlich et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Some other benefits include better perineal muscle relaxation, greater feeling of control and safety over the situation, less abrupt and better transition from the uterus to the environment and a significant risk reduction of vaginal tearing (Dahlen et al, 2013;Shorten, Donsante, & Shorten, 2002;Edlich et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest incidence of intact perinea was found with all-fours position, with kneeling a close second, Rates above 50% were found in the majority of studies (Altman et al, 2007, Shorten et al, 2002, Soong and Barnes, 2005.…”
Section: All-fours and Kneeling Positionsmentioning
confidence: 86%
“…Rates of 2 nd degree tear (or 1 st and 2 nd combined) was around 50% (Altman et al, 2007, Shorten et al, 2002, Soong and Barnes, 2005. Few studies considered anterior trauma but interestingly rates of labial tear were found to be lower with these positions than with waterbirth and other land birth positions , Geissbuehler et al, 2004.…”
Section: All-fours and Kneeling Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence does show the risks and benefits for women according to the position adopted by the women during parturition. It is especially important to minimize the perineal traumas related to the birthing position (5) . Few studies have been done about the risks and benefits of birthing positions during parturition to prevent the maternal mortality attributed to perineal traumas due to different positions.…”
Section: Introductionmentioning
confidence: 99%